Perlindungan Hukum Bagi Para Pihak dalam Kontrak Bisnis Melalui E-Commerce Sebagai Akibat dari Resesi Ekonomi - I Putu Setiawan Ivan Baskara; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
The development of globalization which has become global today, has made several changes in the trading system. E-Commerce or what is often referred to as electronic transaction is a trading activity carried out online by business actors and consumers in conducting trading activities. If a dispute arises between the parties as a result of electronic transactions, especially in Indonesia regarding electronic transactions, it has been specifically regulated in Law no. 11 of 2008 concerning Information and Electronic Transactions in order to provide legal protection to the disputing parties. This study aims to examine the legal arrangements in buying and selling transactions through E-Commerce and revealing legal protection for parties in E-Commerce as a result of the economic recession. In processing research data using normative legal research with a Legislative approach. Sources of data used are primary and secondary legal data obtained through literature study. After the research data has been collected, the last stage is to process the data with descriptive qualitative methods. The results of this study indicate that the legal protection provided to the disputing parties as a result of a business contract carried out using an electronic transaction system is by filing a lawsuit in a commercial court by attaching evidence of an electronic business contract that has been agreed upon by the parties. legal as regulated in Law no. 11 of 2008 concerning Information and Electronic Transactions, which aims to provide protection to the disputing parties in the midst of an economic recession that has hit almost all countries in the world today.